A scientometric analysis of bone cutting tools & methodologies : Mapping the research landscape - Addepalli, Phanindra; Sawangsri, Worapong; Saiful Anwar, Che Ghani (Elsevier Ltd, 2024)
This study undertakes a Scientometric analysis of bone-cutting tools, investigating a corpus of 735 papers from the Scopus database between 1941 and 2023. It employs bibliometric methodologies such as keyword coupling, co-citation, and co-authorship analysis to map the intellectual landscape and collaborative networks within this research domain. The analysis highlights a growing interest and significant advancements in bone-cutting tools, focusing on their design, the materials used, and the cutting processes involved. It identifies key research fronts and trends, such as the emphasis on surgical precision, material innovation, and the optimization of tool performance. Further, the study reveals a broad collaboration among researchers from various disciplines, including engineering, materials science, and medical sciences, reflecting the field's interdisciplinary nature. Despite the progress, the analysis points out several gaps, notably in tool design optimization and the impact of materials on bone health. This comprehensive review not only charts the evolution of bone-cutting tool research but also calls attention to areas requiring further investigation, aiming to inspire future studies that address these identified gaps and enhance surgical outcomes.